Advancements in 13C isotope tracking of synergistic substrate co-utilization in Pseudomonas species and implications for biotechnology applications. (August 2020) - Mendonca, Caroll M; Wilkes, Rebecca A; Aristilde, Ludmilla
Graphical abstract: Highlights: Pseudomonas species exhibit a distinct cyclic pathway for carbohydrate metabolism. ILEs have been used to elucidate carbon metabolism in Pseudomonas species. ILEs characterize the metabolic network during co-utilization of multiple substrates. ILEs can optimize the engineering of Pseudomonas species as biocatalytic platforms. Abstract : Pseudomonads are well-known to thrive in diverse and complex nutritional habitats, and these capabilities make Pseudomonas species attractive as whole-cell biocatalysts. Industrial bioconversion processes often rely on complex uptake and synergistic metabolic systems due to the presence of varied carbon substrates in nutrient feedstocks. Isotope labeling experiments (ILEs) are emerging techniques used to elucidate cell metabolism following feeding on isotopically enriched substrates and are pivotal to the understanding of carbon partitioning during co-utilization. In this review, we highlight the applications of ILEs to decipher the metabolic networks in Pseudomonas species and evaluate their relevance in optimizing biocatalytic platforms.